1959
DOI: 10.1126/science.129.3364.1649
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Antibodies

Abstract: An antibody is a specific globulin which appears in the serum of an animal after the introduction of a foreign substance, an antigen (1). Each of the many globulins is specified by its reaction with a particular antigen (2). Our present concern is to formulate a plausible mechanism for the role of the antigen in evoking large amounts of a specific complementary globulin. An important element of any theory of antibody formation is its interpretation of selfrecognition, the means by which an organism discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
133
0
1

Year Published

1960
1960
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 640 publications
(144 citation statements)
references
References 37 publications
9
133
0
1
Order By: Relevance
“…The studies concluded that there was a period during the ontogeny of lymphocytes when binding of receptors to antigen resulted in cell death, rather than activation, proliferation and development into effector cells. The results were consistent with early proposals on immunological tolerance by Burnet [4] and Lederberg [5], even though at that time information on primary lymphoid organs and lymphocyte turnover was scarce. It is not surprising, therefore, that these results raised many questions some of which I address in this article.…”
Section: Introductionsupporting
confidence: 89%
“…The studies concluded that there was a period during the ontogeny of lymphocytes when binding of receptors to antigen resulted in cell death, rather than activation, proliferation and development into effector cells. The results were consistent with early proposals on immunological tolerance by Burnet [4] and Lederberg [5], even though at that time information on primary lymphoid organs and lymphocyte turnover was scarce. It is not surprising, therefore, that these results raised many questions some of which I address in this article.…”
Section: Introductionsupporting
confidence: 89%
“…Clonal deletion models have been proposed to account for a given organism's tolerance to self constituents (22)(23)(24)(25). Such models suggest that at some time during the maturational differentiation of lymphocytes into immunocompetent cells, there is a sensitive stage whereby contact with antigen results in specific inactivation.…”
Section: Resultsmentioning
confidence: 99%
“…In the 1950s, SHM was proposed as a central player in the immune system either to improve the primary repertoire or to mature a specific immune response 30,31 . It was not until decades later that mutations were actually observed, first in the immunoglobulin protein 32 and then at the DNA level [33][34][35][36] , providing proof that a process of adaptive mutation targeted to a single locus, not observed in any other living organism, was co-opted by the immune system.…”
Section: Somatic Hypermutation and Dna Polymerasesmentioning
confidence: 99%